A bioorthogonal methylene blue derived probe for targeted photoacoustic imaging - Afaf R. Genady; Samantha R. Slikboer; Rowan Swann; Kevin Wyszatko; Nancy Janzen; Luis Rafael Silva; Mohamed E. El-Zaria; Saman Sadeghi; John F. Valliant (Elsevier, 2022)
Photoacoustic (PA) imaging is a nonradioactive and noninvasive imaging modality that can volumetrically map the distribution of photo-absorbing molecules with deeper tissue penetration than optical modalities. Here, we report on a convenient strategy to synthesize a modular methylene blue tetrazine (MB-Tz) PA imaging agent and a trans-cyclooctene (TCO)-labeled bisphosphonate (TCO-BP) calcium metabolism targeting vector. PA imaging of MB-Tz pre-clicked to TCO-BP demonstrated significant signal in regions of active bone metabolism (knee and shoulder joints) at 1 ​h post-injection. Targeting validation and whole-body biodistribution studies were carried out with the radiolabeled pre-clicked product of MB-Tz with 99mTc-TCO-BP, confirming uptake in knees and shoulders at 1 ​h post-injection.